Characterization of the Rate of Injection of Diesel Solenoid Injectors Operated in the Multiple Injection Strategy: A Comparison of the Spray Momentum and Bosch Tube Methods - Aljohani, Bassam S.; Ben Houidi, Moez; Du, Jianguo; Dyuisenakhmetov, Aibolat; Mohan, Balaji; AlRamadan, Abdullah; Roberts, William L. (Frontiers in Mechanical Engineering, 2022)
Multiple injection strategies can be used for controlling the heat release rate, particularly in compression ignition engine configuration. This can mitigate the heat transfer losses and overcome the limitation related to the maximum pressure allowed for a particular engine. Controlling heat release with repetitive injections requires precise characterization of the fuel injection rates. In such a configuration, the injector used should be characterized for its hydraulic delay, rate of injection, and the effect of dwell timing with multiple injections. This paper investigates the fuel injection behavior of a high flow-rate solenoid injector operated with single and double injections. Two characterization methods, the momentum flux, and the Bosch tube are used and compared to investigate their suitability with the multiple injection strategies. Experiments with single injection are conducted by varying the Energizing Timing (ET) from 0.5 up to 2 ms. The tests with multiple injections (i.e., double injections) are conducted with a fixed ET of 0.5 ms while the dwell times (δt) are varied from 0.1 up to 1 ms. All tests are performed at 500, 1000, 1500, and 2000 bar rail pressures. Depending on the injection pressure, the injector’s needle could not fully close with short dwell times and the injections are merged. The momentum flux method have faster ramp-up and decaying and more oscillations in the quasi-steady state phase compared to the Bosch tube method. The effective duration of injection is overpredicted with the Bosch tube method. The momentum flux method is demonstrated to be more suitable for measuring the ROI of multiple injection strategies.